Financial liberalisation : its relevance and experience in the Caribbean - Ould El Hadj, Sidya ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1996)
Examines the policies of financial restrictions and some of their economic implications. Looks at these restricting interrelationships with macroeconomic policies with particular refernece to Guyana, Jamaica and Trinidad and Tobago. Considers financial liberalisation in these three countries.